Age Estimation in Brazilian Adults Using the Pulp/Tooth Ratio of the Maxillary Canine and Mandibular Second Premolar - Nery-Neto, Ismar; Guedes, Orlando Aguirre; Estrela, Lucas Rodrigues de Araújo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Estrela, Cyntia Rodrigues de Araújo; Estrela, Carlos (MDPI, 2024)
(1) Background/Objectives: Accurate determination of chronological age is crucial in legal dental identification. This study aimed to compare the effectiveness of different formulas in estimating the age of a Brazilian subpopulation by analyzing the pulp/tooth ratio of the maxillary canine and mandibular second premolar in panoramic and periapical radiographs. (2) Methods: The sample consisted of panoramic and periapical radiographs of 247 individuals. The file of each radiograph was opened in the Adobe Photoshop CS4® program to outline and obtain values in pixels for calculating the pulp/tooth ratio. Statistical analysis was conducted using the SPSS program, with a significance level set at 5%. (3) Results: The interclass correlation coefficient demonstrated excellent intra-observer agreement (0.990–0.999). The determination coefficients (R2) suggested that only 30–35% of the actual age results could be explained by the pulp/tooth ratio. The smallest differences were observed with Cameriere’s formula for the mandibular second premolar on panoramic radiographs (+4.1 years). The greatest differences were found with the formulas for the mandibular second premolar in panoramic radiographs of the Korean (+12.5 years) and Portuguese (−12.1 years) populations. (4) Conclusions: The equations employed showed little agreement between the actual age and the estimated age.
Keywords: age estimation by teeth; forensic dental radiography; forensic dentistry; forensic science; human identification